Phenomenological Approach of Robbery with Special Overview in the Basic Court in Gjilan- Branch in Vitia during the Period 2013-2017: Array - Aliu, Albana (Acta Universitatis Danubius. Juridica, 2020)
For the purpose of describing, studying, analyzing the features of the manifestation of crime or phenomenology that is otherwise known as a study of external symptoms affecting internal events related to robbery, we will look through reviewing and analyzing the volume, the dynamics and structure of this type of criminality, the time, the place and the means of committing robbery. Then also the study and analysis of robbery if they are carried out through their cooperation and union, as well as some important features of the perpetrator, social features such as the age of the perpetrator, the sex of the perpetrator, the profession, the level of education, recidivism and so on and in this way it will be easier for us to understand these phenomenological factors.